1991
DOI: 10.1021/bi00102a010
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a chaperonin to the folding intermediates of lactate dehydrogenase

Abstract: When Bacillus stearothermophilus LDH dimer is incubated with increasing concentrations of the denaturant guanidinium chloride, three distinct unfolded states of the molecule are observed at equilibrium [Smith, C. J., et al. (1991) Biochemistry 30, 1028-1036]. The kinetics of LDH refolding are consistent with an unbranched progression through these states. The Escherichia coli chaperonin, GroEL, binds with high affinity to the completely denatured form and more weakly to the earliest folding intermediate, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 27 publications
7
123
1
Order By: Relevance
“…These experiments show that target proteins bind strongly to chaperonin only when the latter is in the ADPbound state. Our data support the notion that the role of ATP hydrolysis is to act as a switch between two conformational states (3,23): one (the ADP-bound form) has the ability to bind unfolded target proteins with high affinity (i.e., less than 0.1 rLM), while the other (the ATP-bound form) cannot. Structural differences between chaperonin forms have already been noted from electron microscopic analyses (16,41).…”
Section: Discussionsupporting
confidence: 85%
“…These experiments show that target proteins bind strongly to chaperonin only when the latter is in the ADPbound state. Our data support the notion that the role of ATP hydrolysis is to act as a switch between two conformational states (3,23): one (the ADP-bound form) has the ability to bind unfolded target proteins with high affinity (i.e., less than 0.1 rLM), while the other (the ATP-bound form) cannot. Structural differences between chaperonin forms have already been noted from electron microscopic analyses (16,41).…”
Section: Discussionsupporting
confidence: 85%
“…In another example, studies of refolding of a thermophilic lactate dehydrogenase (LDH) showed that different intermediate states could be populated upon dilution from various concentrations of guanidine hydrochloride. Only the refolding protein from guanidine concentrations producing either complete denaturation or an early intermediate form, a collapsed, molten globule-like state, interacted with GroEL (Badcoe et al, 1991). By contrast, neither a later intermediate, with more secondary structure, nor the folded monomer was bound by GroEL.…”
Section: Conformations Recognized By Groelmentioning
confidence: 93%
“…The interaction of GroEL with unfolded RUBISCO occurred at a similar rate of 3.5 X IO7 M" s" (Roy et al, 1992). Two early unfolded intermediates of LDH (from Bacillus stearothermophilus) associated considerably more slowly with GroEL, with rate constants of 5 X IO5 M" s-l (Badcoe et al, 1991). The association rates of small unfolded polypeptides with GroEL have also been estimated, ranging from >IO8 M" s-I , approaching diffusion-controlled limits, for barnase (Gray & Fersht, 1993) to 0.2-1 X IO6 M" s-' for apo-a-lactalbumin in the reduced or oxidized molten globule state, respectively (Murai et al, 1995;Katsumata et al, 1996).…”
Section: Conformations Recognized By Groelmentioning
confidence: 94%
See 1 more Smart Citation
“…The GroEL chaperonin is overexpressed by bacteria on cell stress and frequently co-purifies with recombi- nant fusion proteins. The binding of ATP to GroEL has been shown to induce a conformational change from a tight-binding form of the protein to a weak-binding form (24). To remove the co-purifying GroEL we included an ATP washing step in the purification procedure (25).…”
Section: Purification Of a Gst-he2mentioning
confidence: 99%